Peranan Pemerintah Desa dalam Meningkatkan Kualitas Pelayanan Administrasi kepada Masyarakat - Erdipa Panjaitan; Rosmala Dewi; Nina Angelia (Universitas Medan Area, 2019)
Role is a set of expectations imposed on an individual who occupies a certain social position. This study aims to determine the role of village government in improving the quality of administrative services to the community in the Office of Village Head Aek Korsik. The method of research used is a descriptive qualitative method approach that focuses on the role of village government in improving the quality of administrative services to the community at the Head Office of Aek Korsik Village Aek Kuo Sub-district, North Labuhanbatu Regency. The results showed that the quality of administrative services in the Head Office of Aek Korsik Village Aek Kuo Sub-district, North Labuhanbatu Regency has applied Tangible, Reliability, Responsiveness, Assurance, and Emphaty dimensions and their indicators. However, there are still some indicators that have not run in accordance with the expectations of the community, including the inconvenience of service places including facilities and infrastructure that have not been complete, the employee has not effectively used SOP (Standard Operating Procedure) in the service process, and there are still employees who are not friendly in the service process.